Roles of Heparan Sulfate Sulfation in Dentinogenesis - Hayano, Satoru (American Society for Biochemistry and Molecular Biology, 2012)
Cell surface heparan sulfate (HS) is an essential regulator of cell signaling and development. HS traps signaling molecules, like Wnt in the glycosaminoglycan side chains of HS proteoglycans (HSPGs), and regulates their functions. Endosulfatases Sulf1 and Sulf2 are secreted at the cell surface to selectively remove 6-O-sulfate groups from HSPGs, thereby modifying the affinity of cell surface HSPGs for its ligands. This study provides molecular evidence for the functional roles of HSPG sulfation and desulfation in dentinogenesis. We show that odontogenic cells are highly sulfated on the cell surface and become desulfated during their differentiation to odontoblasts, which produce tooth dentin. Sulf1/Sulf2 double null mutant mice exhibit a thin dentin matrix and short roots combined with reduced expression of dentin sialophosphoprotein (Dspp) mRNA, encoding a dentin-specific extracellular matrix precursor protein, whereas single Sulf mutants do not show such defective phenotypes. In odontoblast cell lines, Dspp mRNA expression is potentiated by the activation of the Wnt canonical signaling pathway. In addition, pharmacological interference with HS sulfation promotes Dspp mRNA expression through activation of Wnt signaling. On the contrary, the silencing of Sulf suppresses the Wnt signaling pathway and subsequently Dspp mRNA expression. We also show that Wnt10a protein binds to cell surface HSPGs in odontoblasts, and interference with HS sulfation decreases the binding affinity of Wnt10a for HSPGs, which facilitates the binding of Wnt10a to its receptor and potentiates the Wnt signaling pathway, thereby up-regulating Dspp mRNA expression. These results demonstrate that Sulf-mediated desulfation of cellular HSPGs is an important modification that is critical for the activation of the Wnt signaling in odontoblasts and for production of the dentin matrix.